Extracellular vesicles: a rising star for therapeutics and drug delivery - Du, Shuang; Guan, Yucheng; Xie, Aihua; Yan, Zhao; Gao, Sijia; Li, Weirong; Rao, Lang; Chen, Xiaojia; Chen, Tongkai (Journal of nanobiotechnology, 2023)
Extracellular vesicles (EVs) are nano-sized, natural, cell-derived vesicles that contain the same nucleic acids, proteins, and lipids as their source cells. Thus, they can serve as natural carriers for therapeutic agents and drugs, and have many advantages over conventional nanocarriers, including their low immunogenicity, good biocompatibility, natural blood – brain barrier penetration, and capacity for gene delivery. This review first introduces the classification of EVs and then discusses several currently popular methods for isolating and purifying EVs, EVs-mediated drug delivery, and the functionalization of EVs as carriers. Thereby, it provides new avenues for the development of EVs-based therapeutic strategies in different fields of medicine. Finally, it highlights some challenges and future perspectives with regard to the clinical application of EVs. Graphical Abstract Highlights Various current techniques for isolating extracellular vesicles are reviewed, and their advantages and disadvantages are compared. An overview of the strategies used for the modification of extracellular vesicles and their application as delivery systems or therapeutic agents in different diseases is provided. Several challenges in the clinical application of extracellular vesicles-based nanoplatforms are discussed, along with solutions for their implementation as a promising therapeutic tool.